Market accessibility, bond ETFs, and liquidity - Holden, Craig W; Nam, Jayoung (Review of Finance, 2024)
Abstract We develop a stylized model that generates the following empirical predictions: the less (more) accessible the underlying market is ex ante, the more its liquidity improves (deteriorates) when basket trading becomes available. We empirically test these predictions using corporate bonds before and after the introduction of exchange-traded funds. Consistent with the model’s prediction, liquidity improvement is larger for highly arbitraged, low-volume, and high-yield bonds, and for 144A bonds to which retail investor access is prohibited by law. Our article leads to a more nuanced understanding of the impact of basket security introduction than previous research suggested.